Piezoelectric properties of individual nanocrystallites of Ba0.85Ca0.15Zr0.1Ti0.9O3 obtained by oxalate precursor route1. Issue 18 (14th May 2015) - Bharathi, P.; Thomas, P.; Varma, K. B. R.
<x xml:space="preserve">Abstract</x> Ferroelectric domain pattern and piezoresponse (d33) versus DC bias voltage for the BCZT nanocrystalline powder.